Experiential Interiors for Growth-Oriented Brands: Evaluating a Coffee Chain's Interim Concept Design - Suzan Girginkaya Akdağ; Pınar Sunar Bükülmez; Gamze Ekin (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This study investigates the interplay between interior design and customer experience in shaping marketing strategies, with a specific focus on a growth-oriented coffee chain’s development of a new interior concept for future stores. The analysis is guided by the Service Opportunity Matrix (SOM), a strategic framework in business and service management that facilitates a systematic understanding of service processes.  A multi-site case study was conducted across distinct store locations, employing contextual inquiries, on-site interviews, and a comprehensive analysis of the customer journey. Key interior touchpoints—awareness & attract, purchase & pick-up, and eat-drink & experience—were identified and examined to uncover critical pain points within the customer experience. Mapping these areas of improvement onto the SOM framework revealed the necessity for a cohesive, integrated strategy that optimizes each touchpoint across both temporal and spatial dimensions. The findings highlight the critical need to align service environment design with operational efficiency and brand authenticity to ensure consistent, exceptional customer experiences that support sustainable economic growth.